1996
DOI: 10.1038/bjc.1996.498
|View full text |Cite
|
Sign up to set email alerts
|

A randomised dose escalation study of subcutaneous interleukin 2 with and without levamisole in patients with metastatic renal cell carcinoma or malignant melanoma

Abstract: Summary We have examined the efficacy, toxicity and host immunological response of two different dose schedules of interleukin2 (IL-2) given subcutaneously, daily for 3 months in patients with renal cell carcinoma (RCC) and neopterin concentration. Two patients with metastatic melanoma, one in each study, responded (11.8%); both received IL-2 alone. Observations of immunological parameters showed that treatment with subcutaneous IL-2 resulted in a significant rise in the percentage of PBLs bearing CD25, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Nevertheless, more recent studies have somehow questioned the efficacy of levamisole as an immunostimulant (e.g. : Toivanen et al 1981;Webster et al 1982;Aymard et al 1984;Schiller et al 1991;Ahmed et al 1996). Likewise, studies questioned the efficacy of levamisole in the treatment of rheumatoid arthritis (Dinai and Pras 1975) or skin infections (Chang and Fiumara 1978;Seidlin and Straus 1984;Sanchez 2000).…”
Section: Side Effects Of Tetramisole and Levamisole Therapiesmentioning
confidence: 93%
“…Nevertheless, more recent studies have somehow questioned the efficacy of levamisole as an immunostimulant (e.g. : Toivanen et al 1981;Webster et al 1982;Aymard et al 1984;Schiller et al 1991;Ahmed et al 1996). Likewise, studies questioned the efficacy of levamisole in the treatment of rheumatoid arthritis (Dinai and Pras 1975) or skin infections (Chang and Fiumara 1978;Seidlin and Straus 1984;Sanchez 2000).…”
Section: Side Effects Of Tetramisole and Levamisole Therapiesmentioning
confidence: 93%
“…The fourth study, reported by Quirt et al [20], demonstrated a trend toward a disease-free and overall survival benefit of levamisole, although it was of borderline statistical significance. Levamisole has also been tested in combination with interleukin-2 in two randomized studies of patients with advanced melanoma, but no benefit was achieved [23,24]. No further investigations are planned for this agent.…”
Section: Levamisolementioning
confidence: 95%
“…The fourth study, by Quirt et al [78], did demonstrate a trend towards a disease-free and overall survival benefit of levamisole, although it was of borderline statistical significance. Levamisole has also been tested in combination with interleukin-2 in two randomized studies of patients with advanced melanoma, but no benefit was obtained [81,82]. No further investigations are planned for this agent.…”
Section: Immunostimulantsmentioning
confidence: 96%